Adaptive interest rate modelling - Mengmeng Guo; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
A good description of the dynamics of interest rates is crucial to price derivatives and to hedge corresponding risk. Interest rate modelling in an unstable macroeconomic context motivates one factor models with time varying parameters. In this paper, the local parameter approach is introduced to adaptively estimate interest rate models. This method can be generally used in time varying coefficient parametric models. It is used not only to detect the jumps and structural breaks, but also to choose the largest time homogeneous interval for each time point, such that in this interval, the coefficients are statistically constant. We use this adaptive approach and apply it in simulations and real data. Using the three month treasure bill rate as a proxy of the short rate, we nd that our method can detect both structural changes and stable intervals for homogeneous modelling of the interest rate process. In more unstable macroeconomy periods, the time homogeneous interval can not last long. Furthermore, our approach performs well in long horizon forecasting.
Keywords: E44; G12; G32; N22; 330; CIR model; Interest rate; Local parametric approach; Time homogeneous interval; Adaptive statistical techniques; Zinsstrukturtheorie; Faktorenanalyse; Schätztheorie; Strukturbruch; Theorie; Schätzung; Schatzpapier; Saint Louis (Mo.)